The effect of nanosilver particles on the physicomechanical properties of dental amalgam free of unbound mercury / Chanthiriga Ramasindarum - Chanthiriga, Ramasindarum (2018)
Dental amalgam has been widely used over the past 190 years in dentistry due to its low cost and durability. SilverfilTM was introduced into the Malaysian market in early 2000 as an amalgam free of unbound mercury (Hg). However, a large particle size variation of SilverfilTM alloy is the critical concern raised by its manufacturer. Therefore, the present study focuses on introducing nano-sized silver particles (AgNPs) into the manufacturing process of SilverfilTM in order to enhance its physical and mechanical properties. The aims of this research were first to characterise the SilverfilTM starting materials, followed by synthesis and characterisation of AgNPs, formulation of an experimental nanosilver amalgam based on the conceptual SilverfilTM model, and to finally compare the physical and mechanical characteristics of the optimised experimental nanosilver amalgam with those of SilverfilTM as well as GS80 and Dispersalloy as two other commercially available amalgams. The results obtained via the field emission electron microscopy indicated a particle size distribution in the range of 146-786 nm for the SilverfilTM alloy. Moreover, the X-Ray photoelectron spectroscopy analyses confirmed the absence of unbound Hg in the triturated SilverfilTM, while elements such as copper and tin were present as impurities in the composition of its starting materials. AgNPs were synthesised by reaction of an aqueous silver nitrate (AgNO3) solution with hydrazine hydrate as a reducing agent. The high resolution transmission electron microscopy investigations indicated the formation of AgNPs with polygonal morphology and mean particle size of 34.27±7.38 nm. The crystalline structure and size of AgNPs, investigated respectively by X-ray diffraction and small angle X-Ray scattering, were face centred cubic (FCC) and 54.20 nm. Among varied types of AgNPs synthesised with different AgNO3 concentrations, those produced by a 2 M AgNO3 solution were chosen for formulation of the optimised experimental nanosilver amalgam with the AgNPs:Hg ratio of 1:2.9. The manipulation and handling of the optimised experimental nanosilver iv amalgam were evaluated by two dentists. The optimised experimental nanosilver amalgam was consisted of polygonal-shaped particles with mean particle size of approximately 141.55±52.12 nm and without the presence of unbound Hg in the triturated formulation. According to the XRD analyses, both SilverfilTM and the optimised experimental nanosilver amalgam showed a crystalline structure resembling “moschellandsbergite”, a naturally occurring mineral (Ag2Hg3). The compressive strength, diametral tensile strength, and Vickers microhardness values of the optimised experimental nanosilver amalgam were quantified as after 24 hours and 7 days of incubation in distilled water at 37°C. The compressive strength values measured after 24 hours for the optimised experimental nanosilver amalgam, SilverfilTM, GS80, and Dispersalloy were 380.62±37.10 MPa, 449.66±173.98 MPa, 447.12±18.60 MPa, and 190.68±44.18 MPa, respectively. The diametral tensile strength measured at 24 hours for the optimised experimental nanosilver amalgam was 128.77±63.59 MPa, which was significantly higher than those of SilverfilTM (72.71±10.23 MPa), GS80 (39.32±7.79 MPa), and Dispersalloy (41.66±7.79MPa). On the other hand, GS80 exhibited the highest Vickers microhardness value (233.82±15.68), followed by Dispersalloy (175.38±8.02), and SilverfilTM (103.16±4.39) whereas Vickers microhardness for the optimised experimental nanosilver amalgam was the lowest (89.77±5.55) after 24 hours. Subsequent Bonferroni post hoc tests showed significant differences (P<0.005) between the mean Vickers microhardness values of the tested amalgams after storage for 24 hours and 7 days. In conclusion, although no detectable unbound Hg was present in SilverfilT M, the impurities existing in the starting materials might contribute to its relatively high mechanical strength. The large particle size variation of the SilverfilTM alloy was addressed by utilisation of AgNPs synthesised with a particle size of 18.81±46.12 nm. The optimised experimental nanosilver amalgam showed improved homogeneity and a significantly higher diametral strength compared to SilverfilTM. The AgNPs:Hg ratio of v 1:2.9 was determined as the minimum applicable ratio for producing a well-triturated dental amalgam